Insights into the characteristics and mechanism of vacuum drying technology for municipal sludge processing. (January 2023) - Zhu, Qixiang; Sun, Xiaofeng; Ge, Shifu; Yu, Yang
Abstract: Vacuum drying is an effective approach for sludge treatment and valorization. However, the vacuum drying of sludge has not been industrialized at present. The objective of this study was to elucidate the vacuum drying characteristics of static sludge and crack initiation mechanism. Our results indicate that crusting on the sludge surface under a high vacuum inhibited drying by reducing major cracks at sludge thicknesses of 13.6 and 10.2 mm. The inhibition effect weakened with decreasing sludge thickness. At 6.8 mm, the mean drying rate (VM ) was the lowest at 0.08 MPa, while VM decreased with increasing vacuum degree at thicknesses of 13.6 and 10.2 mm. The decrease in drying rate could be attributed to rapid evaporation on the sludge surface under a high vacuum, leading to crusting, which inhibited crack initiation. VM was raised by 67.9–162.2% from 10.2 to 6.8 mm because the suction force of vacuum on water was much higher than the resistance to water diffusion of small isolation piles at 6.8 mm. Additionally, this study provided essential information to improve existing sludge treatment methods. Graphical abstract: Image 1 Highlights: Vacuum decreased the drying rate of static municipal sludge under some working conditions. The cracks decreased with the increase of vacuum degree. The crack initiation mechanisms varied with different vacuum degrees and sludge thicknesses.